A review of literature on neuro-linguistic programming (NLP) / Syahida Md Zeni ...[et al.] - Md Zeni, Syahida; Azis, Saflina; Mat, Mustafa Kamal; Amat, Mohd Aripin (2016)
Neuro Linguistic Programming (NLP) is a new approach that has been immerged and developed quite recently. It is the combination of three words 'Neuro', 'Linguistic' and 'Programming', which was initially used by psychotherapist, but in an unstructured manner. Nowadays it has become very structured theoretically and technically. There are a number of techniques involve in NLP, which have been developed by its two co-founders, Richard W. Bandler and Dr. John T. Grinder. A number of researchers have explored the literature on NLP, the techniques, usage and advantages. This paper reviews those studies with the aim to look into the advantages of applying NLP in the Malaysian context, especially for teaching and learning. Several areas which have been discussed by previous researchers are included in this study to achieve its objective. Those areas are NLP in teaching and learning, NLP in communication and motivation, and NLP for coaching. There are also few researchers who claim that NLP technique is not as good as claimed by the practitioners, but they also claimed that further research need to be done to prove their findings. In Malaysia, there are very few studies found on NLP as it was popular just within few recent years.